PROFIL KURIKULUM CINTA DALAM PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK - Arif Sholehudin (IEC: Journal of Educational Innovation, 2025)
Strengthening character education has become a strategic issue in contemporary education in response to moral, social, and emotional challenges faced by students. The Love-Based Curriculum is an educational approach that places love as a foundational value for holistic character development. This study aims to describe the profile of the Love-Based Curriculum in strengthening students’ character education, including its conceptual foundation, principles, implementation methods, and developed character values. The research employed a qualitative descriptive approach with data collected through interviews, observations, and document analysis. Research subjects included school leaders, teachers, and students involved in the implementation of the Love-Based Curriculum. The findings indicate that the profile of the Love-Based Curriculum is reflected in the integration of love values into learning planning, instructional practices, school culture, and character-strengthening activities. This curriculum contributes to the development of students’ empathy, tolerance, responsibility, and social and spiritual awareness.